Association between CHFR and PARP-1, and Their Roles in Regulation of Proliferation and Apoptosis of B Cell Lymphoma - Xiao-Dan Liu; Nian-Ju Zheng; Liang Song; Hua Pan; Ai-Qin Song (Analytical Cellular Pathology)
Background. Aberrant methylation of checkpoint with forkhead and ring finger domains (CHFR) was found in B-cell non-Hodgkin lymphoma (NHL), whereas its role in carcinogenesis is not clear. CHFR can control poly (ADP-ribose) polymerase levels by causing its degradation. The study was aimed to explore the roles and mechanisms of CHFR in the pathogenesis of B-cell NHL. Methods. Short hairpin ribonucleic acid (ShRNAs) targeting CHFR and poly (ADP-ribose) polymerase 1 (PARP-1) were transduced into Raji cells, and real-time polymerase chain reaction (PCR) and western blotting were carried out to determine their expression. Afterwards, the CCK-8 assay and flow cytometry were used to evaluate the cell growth and apoptosis. Tumor size and weight were determined using a xenograft model, and decitabine (5-Aza-dC) was used to further determine the methylation status of CHFR through a methylation specificity-PCR assay. Results. 5-Aza-dC-treatment promoted the expression of CHFR and decreased the expression of PARP-1 at both messenger ribonucleic acid (mRNA) and protein levels. 5-Aza-dC also accelerated Raji-cell apoptosis and restrained its growth in vitro and in vivo (P<0.05). These results were contrary to those observed in the shRNA-CHFR group but consistent with those observed in the shRNA-PARP-1 group. The expression profiles of CHFR and PARP-1 in the xenograft model were consistent with those in the cellular model. Treatment with 5-Aza-dC led to demethylation of CHFR in nude mice. Besides, there may be a negative correlation between CHFR and PARP-1 in B-cell NHL cells. Conclusion. Our findings indicated that 5-Aza-dC could lead to the demethylation of the CHFR promoter and suppress Raji cell growth.